Comparative Evaluation of Cytologic and Histologic Grading in Invasive Ductal Carcinoma Breast (GAIMS Journal of Medical Sciences, 2025)
Background: Accurate pathological diagnosis is crucial for further treatment and estimation of an outcome in cases of breast cancer. The cytologic grade may provide information about the aggressive behavior of the tumor, thus guiding optimal therapy with prognostic information. The widely used Nottingham histologic grading method is a tumor grading system with strong prognostic connections.Material and methods: This cross-sectional study was conducted over one year in the Department of Pathology in IGMC, Shimla. Our study aimed to determine the role of Robinson’s grading in cases of primary infiltrating ductal carcinoma, breast, on cytology, confirm and grade the tumor on histopathology, and find the concordance between cytologic and histologic grading.Results: On comparing cytologic and histologic grading, 37(68.5%) cases were graded based on cytology, which is comparable to most of the published data. The cytohistologic correlation was maximum in cases of grade III tumors (80%), followed by grade II tumors (70.2%), and minimum with grade I tumors (58.3%).Conclusion: In this era of neoadjuvant chemotherapy, FNAC reports in cases of breast cancer should be incorporated with grading for prognostication. Considering the present study's data and other comparative studies, it can be concluded that Robinson’s cytologic grading correlates reasonably well with the histologic grading system, especially the grade III tumors, and paves the way for recommending neoadjuvant chemotherapy. Cytologic grading correlates reasonably well with the histologic grading system, especially the grade III tumors, and paves the way for recommending neoadjuvant chemotherapy.